Effects of two different types of luteal support on pregnancy outcomes following antagonist fresh embryo transfer: a retrospective study - Minji De; Lixue Chen; Lin Zeng; Yang Wang; Rui Yang; Rong Li; Hongbin Chi (BMC, 2023)
Abstract Background Only a small number of studies have reported the use of progesterone vaginal gel in combination with dydrogesterone as part of the antagonist protocol for fresh embryo transfer. Therefore, this study aimed to compare the effects of two types of luteal support on pregnancy outcomes following the antagonist protocol for fresh embryo transfer. Methods We performed a retrospective analysis of clinical data from infertile patients who underwent fresh embryo transfer via the antagonist protocol (2785 cycles) between February and July 2019 and between February and July 2021 at the Peking University Third Hospital Reproductive Medicine Centre. According to the luteal support received, the cycle groups were divided into the progesterone vaginal gel group (single medication or VP group; 1170 cycles) and the progesterone vaginal gel plus dydrogesterone group (combination medication or DYD + VP group; 1615 cycles). After propensity score matching, the clinical pregnancy, ongoing pregnancy, early miscarriage, and ectopic pregnancy rates were compared between the two groups. Results In total, 1057 pairs of cycles were successfully matched via propensity scores. The clinical and ongoing pregnancy rates in the combination medication group were significantly higher than those in the single medication group (P < 0.05), whereas no significant differences were noted in the early miscarriage and ectopic pregnancy rates between the two groups (both P > 0.05). Conclusions Combined luteal support after the antagonist protocol is preferred for patients undergoing fresh cycle embryo transfer.